SEEING IS BELIEVING: SERVICE TRANSPARENCY AS A KEY TO ACCOUNTABLE VILLAGE GOVERNANCE - Herlina Manurung; Naufal Afif; Saras Qurrota’ Aini; Siska Dwi Yuniar; Andini Maharani Putri (Universitas Pakuan, 2025)
ABSTRACTThis study aims to investigate the impact of transparency and community participation on perceived accountability in village governance. Using a quantitative approach, data were collected from 46 respondents in Sleman Regency, Indonesia, through a structured questionnaire. The sample was selected using a combination of simple random and stratified sampling methods. The research utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS) for data analysis. The findings reveal that service transparency significantly enhances perceived accountability, while financial transparency has no significant impact. Additionally, trust and participation were found to influence transparency preferences, but they did not mediate the relationship between transparency and accountability. These results highlight the importance of service-oriented transparency in improving governance accountability, suggesting that governments should prioritize visible outcomes over complex financial disclosures. This research contributes to the understanding of citizen-driven governance and offers practical insights for improving local accountability through enhanced service transparency.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh transparansi layanan dan transparansi keuangan terhadap akuntabilitas pemerintahan desa dengan memperhatikan peran kepercayaan dan partisipasi masyarakat sebagai mediator. Penelitian menggunakan pendekatan kuantitatif dengan survei terhadap 46 responden di Kabupaten Sleman, Indonesia. Sampel ditentukan melalui pengambilan sampel acak sederhana dan stratifikasi. Data dianalisis menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS). Hasil penelitian menunjukkan bahwa transparansi layanan berpengaruh signifikan terhadap akuntabilitas, sementara transparansi keuangan tidak menunjukkan pengaruh yang signifikan. Selain itu, meskipun kepercayaan dan partisipasi masyarakat memengaruhi preferensi transparansi, keduanya tidak berperan sebagai mediator dalam hubungan transparansi dan akuntabilitas. Temuan ini menggarisbawahi pentingnya transparansi yang berfokus pada layanan dalam meningkatkan akuntabilitas pemerintahan desa. Implikasi praktis penelitian ini adalah perlunya fokus pada transparansi yang lebih nyata dan terukur dalam pelayanan publik untuk memperbaiki akuntabilitas di tingkat lokal